Darunavir: A Critical Review of Its Properties, Use and Drug Interactions - Ruela Correa, Josilene Chaves [UNESP]; D'Arcy, Deirdre M.; dos Reis Serra, Cristina Helena; Salgado, Hérida Regina Nunes [UNESP] (Karger, 2012)
Darunavir is a synthetic nonpeptidic protease inhibitor which has been shown to be extremely potent against wildtype HIV as well as a large panel of PI-resistant clinical isolates and shows a high genetic barrier to the development of antiretroviral resistance. The treatment of HIV/AIDS requires combinations of multiple antiretroviral drugs. In addition, patients frequently need to coadminister other medications for reasons including the prevention or treatment of opportunistic infections, treatment of concomitant illnesses and management of antiretroviral side effects. Drug interactions have been observed between darunavir and other drugs. New and more comprehensive drug interaction studies will be required since the increase in life expectancy of patients often brings new comorbidities and the concomitant use of different drugs. This paper discusses the impact of the use of darunavir in the treatment of HIV-infected patients, its pharmacological and physical-chemical properties, its drug interactions, and challenges that remain in order to ensure safety and compliance of treatment. Copyright (C) 2012 S. Karger AG, Basel
Keywords: Darunavir; Human immunodeficiency virus; Acquired immune deficiency syndrome; Clinical pharmacokinetics; Drug interactions; Biopharmaceutics classification system